Dossier: infancias indígenas, identificaciones étnico-nacionales y educación: experiencias formativas cotidianas dentro y fuera de las escuelas - Ames, Patricia (2015)
Presentation of the dossier on indigenous childhood, ethnic-national identifications and education: Daily formative experiences inside and outside schools.